2014
DOI: 10.3109/09637486.2014.917150
|View full text |Cite
|
Sign up to set email alerts
|

trans-10,cis-12 Conjugated linoleic acid specifically increases tissue α-tocopherol mediated by PPARγ inhibition in mice

Abstract: C57BL/6J mice were divided into control group (C), CLA, c9t11, or t10c12 groups. CLA and t10c12 significantly increased α-tocopherol levels in the plasma and various tissues in experiment 1. The CLA and t10c12 groups also showed a significant increase in hepatic α-tocopherol transfer protein (α-TTP) levels. In experiment 2, mice were divided into control, CLA, R (rosiglitazone, a PPARγ agonist), or CLA+R groups. Vitamin E levels in the liver, epididymal fat pad, kidney, and plasma were increased by CLA, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…These isomers have shown to exhibit additive, independent, or antagonistic effects (Park and Pariza ). It has been demonstrated that the cis ‐9, trans ‐11 CLA isomer is responsible for anti‐inflammatory effect and inhibition of hepatic sterol regulatory element binding protein‐1c expression (Roche and others ; Moloney and others ), whereas the trans ‐10, cis ‐12 isomer is responsible for body fat reduction, enhancing endurance capacity, increases in tissue α‐tocopherol, and reduction of hepatic apolipoprotein B secretion (Park and others ; Storkson and others ; Kim and others ; Wang and others ).…”
Section: Cla Isomersmentioning
confidence: 99%
“…These isomers have shown to exhibit additive, independent, or antagonistic effects (Park and Pariza ). It has been demonstrated that the cis ‐9, trans ‐11 CLA isomer is responsible for anti‐inflammatory effect and inhibition of hepatic sterol regulatory element binding protein‐1c expression (Roche and others ; Moloney and others ), whereas the trans ‐10, cis ‐12 isomer is responsible for body fat reduction, enhancing endurance capacity, increases in tissue α‐tocopherol, and reduction of hepatic apolipoprotein B secretion (Park and others ; Storkson and others ; Kim and others ; Wang and others ).…”
Section: Cla Isomersmentioning
confidence: 99%